Innovative training management models for advancing teacher competence: A research-based framework for pedagogical development - Sipayung, Regina; Sitanggang, Nathanael; Purba, Saut (Edelweiss Applied Science and Technology, 2025)
The competence of teachers plays a vital role in improving the quality of education in the 21st century. This study explores the development and validation of an innovative training management model aimed at strengthening the pedagogical skills of elementary school teachers. Using the Plomp development model as a framework, the research involved 114 participants selected through purposive sampling. Data collection combined qualitative and quantitative methods, including normality tests, paired sample t-tests, and normalized gain (N-Gain) analysis. The findings indicate that the model is highly feasible, with expert validation scores exceeding 90% and positive feedback from users. Implementation of the model led to significant improvements in teachers’ abilities to plan instruction, conduct educational activities, and integrate technology into learning. The N-Gain results categorized the training as highly effective. These outcomes suggest that the model provides a practical and sustainable approach to professional development. Further research is recommended to explore broader application and long-term impacts.